2021
DOI: 10.3390/su13020814
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Family, Behavioral, and Neuropsychological Factors to Long-Term Functional Outcomes in Young Adults with ADHD: A 12-Year Follow-Up Study

Abstract: The persistent nature of attention deficit hyperactivity disorder (ADHD) and the role of behavioral factors in its continuity have been widely documented in the literature. However, less is known about the role of early family and neuropsychological factors in predicting later adaptive functioning and quality of life in individuals with ADHD. This study aimed to analyze the contribution of early family, behavioral, and neuropsychological factors to long-term functional outcomes in young adults with ADHD. Famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Social support, which includes support from extended family and friends, is considered one of the important coping resources for single mothers having CWSNs. Parents who are optimistic and have support from friends and family are more likely to adopt a problem-focused and active-coping strategy to deal with the challenges of raising a CWSNs (Miranda et al, 2021). Religious faith as a coping strategy has also been perceived as having positive effects in combating stress and enhancing healthy mental health.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…Social support, which includes support from extended family and friends, is considered one of the important coping resources for single mothers having CWSNs. Parents who are optimistic and have support from friends and family are more likely to adopt a problem-focused and active-coping strategy to deal with the challenges of raising a CWSNs (Miranda et al, 2021). Religious faith as a coping strategy has also been perceived as having positive effects in combating stress and enhancing healthy mental health.…”
Section: Coping Strategiesmentioning
confidence: 99%
“…[16] Further, longitudinal work looking at adult outcomes of childhood ADHD have concluded that family, behavioral, and neuropsychological factors not only contribute to later quality of life and success outcomes (i.e., occupational, education attainment, executive functioning) but are areas of research that will be critical for efficacious ADHD interventions in the future. [17] It is possible that treatment outcomes could be improved with a better understanding of the neural underpinnings of ADHD. A better understanding of dysfunctional neural systems may allow for improved and earlier identification of ADHD by providing biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term impairment in childhood ADHD continues into adulthood along domains of psychosocial, educational, and neuropsychological functioning regardless of medication or therapy interventions [16]. Further, longitudinal work looking at adult outcomes of childhood ADHD have concluded that family, behavioral, and neuropsychological factors not only contribute to later quality of life and success outcomes (i.e., occupational, education attainment, executive functioning) but are areas of research that will be critical for efficacious ADHD interventions in the future [17]. It is possible that treatment outcomes could be improved with a better understanding of the neural underpinnings of ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…One article shows the effects of an intervention based on perceptual-motor skills' reconstruction to improve the executive functions and key symptoms in ADHD, based on a sample of 50 students (8-10 years) equally distributed in a control and an experimental group, following a pretest-posttest design [18]. Additionally, this Special Issue includes a follow-up study based on a 12-year time lapse, where the main aim is to examine the role of family and behavioral and neuropsychological factors when predicting long-term functional outcomes in young adults with ADHD [19]. Last but not least, the bibliometric review that closes this Special Issue provides evidence on the communication gap that still exists between the scientific fields of Psychiatry/Psychology and Education concerning classroom management of ADHD, that is, between science and practice [20].…”
mentioning
confidence: 99%